Korelasi antara jumlah publikasi dosen dengan penggunaan layanan RemoteXs Perpustakaan UNAIR - Nugroho, Prasetyo Adi (Daluang: Journal of Library and Information Science, 2022)
Introduction. Social restrictions due to COVID-19 have made it difficult to obtain research data and literature to support publication activities. Universitas Airlangga (UNAIR) provides Remotex facilities or remote repository access, where academics can read and download journals of international repute. This paper aims to analyze whether there is a relationship between RemoteXs access by faculty and the number of publications on Scopus.Methodology. This study uses statistical data on the number of times the repository is accessed by the faculty. a sample of the number of papers was also taken from the Scopus website. Data were analyzed by the Pearson Correlation method.Results and discussion. The results of the study show that the number of lecturers' accesses has no correlation with the number of publications. Meanwhile, the total repository access at the faculty is strongly correlated with the number of publications.Conclusion. There is no relationship to how many times the number of RemoteXs access publications on Scopus. However, there is a relationship with the faculty, this is because of the doctoral program in the faculty that is required for publication.